Phenolic acids and derivatives: studies on the relationship among structure, radical scavenging activity, and physicochemical parameters - Silva, Francisco A. M. (2019)
The antiradical activity of caffeic acid (1), dihydrocaffeic acid (5), and their corresponding n-alkyl esters was evaluated by using the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH(*)) method. Dihydrocaffeic acid (5) was the most potent compound, having an antiradical effect higher than that of (+/-)-alpha-tocopherol, whereas caffeic acid (1) was less efficient. Esterification of the carboxyl group of dihydrocaffeic acid (5) had a dramatic effect on its antiradical potency, but similar effects were not observed for caffeic acid (1) derivatives. The n-alkyl esters of both phenolic series had similar potencies, and their antiradical activities were independent of the alkyl chain length. Dose-dependent scavenger effects were found in both series. Acid-base properties of the compounds, evaluated by using potentiometry and spectrophotometry, showed that the catechol moiety had pK(a2) and pK(a3) values of 9. 24-9.02 and 11.38-10.99 in the dihydrocaffeic series and 8.48-8.24 and 11.38-11.07 in the caffeic series, respectively. Antiradical activity and pK(a) values of the compounds were not related.